Friction Stir Spot Extrusion Joining With Its Metal Flow Investigation - Mohanad Kadhim Mejbel; Isam Tareq Abdullah (Advances in Materials Science and Engineering)
This study aims to extrude a portion of an Al sheet through a steel hole shaped like a rivet to assemble an Al and a preholed steel sheet by a mechanical interlock. This will be accomplished by joining the two materials together. AA6061 and AISI1006 sheets were assembled using a lap arrangement, with the steel preholed sheet placed below the aluminum sheet. A rivet head die was placed beneath the hole of the steel sheet. To attach the parts, a spinning tool used friction stir spot extrusion to force the Al through the die and into the steel hole. The influence of the hole diameter, tool depth of plunge, and revolving speed on the dimensions of the rivet head (thickness and diameter) and joint strength of shear were analyzed by the design of the experiment’s technique. The joint microstructure was investigated. An extrusion of the Al metal in the form of a rivet was conducted successfully. The diameter of the hole in the steel sheet revealed a critical influence on the joints’ force of shear and the dimensions of the rivet head. Raising the tool depth of the plunge increases the joint’s strength of shear. Due to the shearing of the extruded aluminum at the steel hole surface, the joined sheets failed. This occurred without the produced rivet head being detached. A mechanical interlock was the joining mechanism without intermetallic compounds forming between the two materials. AISI 1006 preholed steel and AA6061 sheets were assembled for the first time by extruding the Al with a flat rivet shape. The joint’s shear strength efficiency was 94.6%.